Perancangan Antarmuka Pengguna Aplikasi Rencana Pembelajaran Semester (RPS) berbasis Website menggunakan Goal Directed Design - Ammar Gunya Pratomo; Issa Arwani; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Semester Study Plan or Rencana Pembelajaran Semester (RPS) in Indonesia is a study plan document for one whole semester created by lecturer or a group of lecturer as a guide to reach the study goal for students. However, every documents created by lecturers doesnt have a standart even though they already received a template to create the study plan. Based on that problem, the lecturers need a system to make the documents easier to create according to the standarts. To create a good information system we need to focus on the user interface because with great Ui the system we create can be more appealing and keeping the user to stay and use the system. This research will create a web based user interface design using goal directed design. In this method there are six steps to create a design, the steps are research, modelling, requirement framework, refinement, and support. FIGMA is chosen to implement the UI prototype. After the protytpe is ready, usability evaluation will be conducted. There are two versions of this prototype, the first one with 69 score and the second with 75 score. Based on the results, it is recommended to use version two of the design with more improvements to increase the user interface usability.